Scratching the Itch: The role of venereal disease in the settling of the American West - Edgar, Joshua, D. (Kansas State University. Dept. of History, 2017)
For many, the frontier conjures up pictures of cowboys and shootouts. However, for those who lived through the frontier period, the picture was painted with a much bleaker brush. The constant threat of venereal disease played a major role in shaping the frontier. Whether it be through its drain on the military, its widespread effect on the national social fabric, or its rapid decimation of communities, sexually transmitted diseases were major factors in how people made decisions and where they settled. Venereal diseases can also be used to isolate and then extrapolate the changing moral landscape of both the frontier and America at the change of the 20th century. In the broad spectrum, the study of venereal diseases can be used a tool to expand our knowledge of not only the medical field, but can also develop our understanding of how modern attitudes regarding sexually transmitted infections were influenced by the past.
Keywords: Venereal; Morality; Prostitution; Military; Frontier